Relationship between fear of COVID‐19 and mental health of Chinese nurses: The mediating effects of psychological capital and burnout - Chengxiang Liu; Sainan Li; Juan Zhou; Miao Zhang; Hong Chen (Wiley, 2024)
Abstract Aim The aim of the study was to investigate the correlation between fear of COVID‐19 and mental health of nurses and the effects of psychological capital and burnout in this relation. Design A cross‐sectional study. Methods The online surveys were conducted among mainland Chinese nurses. Participants (n = 445; average age 32.89 ± 6.76 years) completed an online‐questionnaire based on the Fear of COVID‐19 Scale, the Psychological Capital Scale, Maslach Burnout Inventory Human Services Survey for Medical Professionals Scale and the 12‐Item Short Form Health Survey. Data analysis was conducted by Pearson's correlation analysis, Harman single‐factor test and the bootstrap method for mediating effect testing. Results (1) The study demonstrated a significant direct effect of fear of COVID‐19 on nurses' mental health, as well as on mediating factors such as burnout and psychological capital. (2) Regression analyses confirmed that while psychological capital bolstered mental health, burnout undermined it, with fear of COVID‐19 further imposing a negative influence. (3) Fear of COVID‐19 exerted an effect on the mental health of nurses by the independent and chain intermediary functions of psychological capital and burnout, resulting in a total mediating effect of −0.233.